Cartoonization of photographs - Lee, Kun Hup (Nanyang Technological University, 2021)
This project aims to use image processing techniques to achieve cartoonization of photographs. All the algorithms will be developed in MATLAB. Firstly, an algorithm based on the region growing method will be developed and used in this project for the purpose of image segmentation. Secondly, various edge detection techniques such as Canny method will be explored and tested for use in conjunction with the region growing method to achieve cartoonization. Lastly, a simple Graphical User Interface (GUI) will be developed for the ease of use of the algorithms. This will be done in MATLAB’s Graphical User Interface Development Environment (GUIDE)